A morphologic and immunohistochemical analysis of gastric adenocarcinoma with regard to the presence of E-cadherin and localisation of β-catenin staining - Roberts, Riyaadh (Division of Anatomical Pathology, 2014)
Includes abstract. Includes bibliographical references.